1996
DOI: 10.1074/jbc.271.25.15069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endothelial Nitric-oxide Synthase during Hypoxia

Abstract: The mechanism by which nitric-oxide (NO) production increases during hypoxia is unknown. To explore the effect of hypoxia upon endothelial nitric-oxide synthase (ecNOS) activity and expression, we exposed bovine aortic endothelial cells (BAEC) to hypoxia (1% O 2 ) for 0 -24 h and measured levels of ecNOS mRNA, protein, and activity. The amount of ecNOS mRNA increases to more than twice the basal level after 6 h of hypoxia. Incubation of BAEC with actinomycin D during hypoxia prevents this increase, demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
2
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(121 citation statements)
references
References 42 publications
9
106
2
4
Order By: Relevance
“…Our finding that VEGF-induced vascular dysfunction is prevented by NOS inhibitors is consistent with evidence that a relative or absolute increase in nitric oxide mediates vascular dysfunction in diabetic rats and in retina and nerve of nondiabetic rats with acute hyperglycemia (27,55). Our hypothesis that vascular dysfunction induced by early diabetes is mediated by increased nitric oxide production as a consequence of "hypoxia-like" cytosolic reductive stress is supported by evidence that true hypoxia increases endothelial NOS mRNA, NOS enzyme activity, and increased NO production (56,57) and that blood flow increases immediately in response to mild hypoxia.…”
Section: Discussionsupporting
confidence: 70%
“…Our finding that VEGF-induced vascular dysfunction is prevented by NOS inhibitors is consistent with evidence that a relative or absolute increase in nitric oxide mediates vascular dysfunction in diabetic rats and in retina and nerve of nondiabetic rats with acute hyperglycemia (27,55). Our hypothesis that vascular dysfunction induced by early diabetes is mediated by increased nitric oxide production as a consequence of "hypoxia-like" cytosolic reductive stress is supported by evidence that true hypoxia increases endothelial NOS mRNA, NOS enzyme activity, and increased NO production (56,57) and that blood flow increases immediately in response to mild hypoxia.…”
Section: Discussionsupporting
confidence: 70%
“…Hypoxic incubation (zero O 2 for 24 hours) decreased eNOS activity and expression in endothelial cells from human umbilical cords 9 and saphenous veins. 21,22 In contrast, Arnet et al 23 reported that eNOS activity and expression were increased in bovine aortic endothelial cells after 24 hours of incubation at 1% O 2 . This variability probably reflects differences in species and vascular beds, methods used to maintain the cells, and duration and severity of the hypoxic exposures.…”
Section: Discussionmentioning
confidence: 93%
“…Some animal studies demonstrate that NO production is increased in hypoxia-induced pulmonary hypertension, 25,26 whereas human studies indicate that eNOS expression and activity are substantially reduced. 3 These discrepancies may be due in part to the different causes and stages in the development of pulmonary hypertension and to differences between in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 99%